Enhancing the Cognitive Effects of Flavonoids With Physical Activity: Is There a Case for the Gut Microbiome? - Cheatham, Carol L.; Nieman, David C.; Neilson, Andrew P.; Lila, Mary Ann (Frontiers in Neuroscience, 2022)
Age-related cognitive changes can be the first indication of the progression to dementias, such as Alzheimer’s. These changes may be driven by a complex interaction of factors including diet, activity levels, genetics, and environment. Here we review the evidence supporting relationships between flavonoids, physical activity, and brain function. Recent in vivo experiments and human clinical trials have shown that flavonoid-rich foods can inhibit neuroinflammation and enhance cognitive performance. Improved cognition has also been correlated with a physically-active lifestyle, and with the functionality and diversity of the gut microbiome. The great majority (+90%) of dietary flavonoids are biotransformed into phytoactive phenolic metabolites at the gut microbiome level prior to absorption, and these prebiotic flavonoids modulate microbiota profiles and diversity. Health-relevant outcomes from flavonoid ingestion may only be realized in the presence of a robust microbiome. Moderate-to-vigorous physical activity (MVPA) accelerates the catabolism and uptake of these gut-derived anti-inflammatory and immunomodulatory metabolites into circulation. The gut microbiome exerts a profound influence on cognitive function; moderate exercise and flavonoid intake influence cognitive benefits; and exercise and flavonoid intake influence the microbiome. We conclude that there is a potential for combined impacts of flavonoid intake and physical exertion on cognitive function, as modulated by the gut microbiome, and that the combination of a flavonoid-rich diet and routine aerobic exercise may potentiate cognitive benefits and reduce cognitive decline in an aging population, via mechanisms mediated by the gut microbiome.